Bringing the 'social' in from the cold: towards a social history of American intelligence. Issue 5 (3rd September 2021) - Moran, Christopher Richard; Hammond, Andrew
Abstract: The subject of American intelligence has traditionally been studied by people who would identify themselves as diplomatic historians, International Relations scholars, or a combination of both. As a result, the history of American intelligence is a rather 'top down' history. It is a history of Beltway politics, NSC meetings, and the private interactions between intelligence chiefs and policymakers. It is the history of major operations rather than of the everyday. It is a history of landmark documents rather than the workaday. Yet, the history of American intelligence is also the history of social relationships, social structures, and social hierarchies. The aim of this article, as an Introduction to the following Special Issue, is to sketch what a 'social' history of American intelligence would look like. In short, this article asks: how would a social historian write the history of American intelligence?